FOREIGN LANGUAGE LEARNING IN OPTIONAL STUDY COURSES AT LASE - Malahova, Ludmila; Boge, Iveta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Nowadays to be competitive in labor market foreign language knowledge and skills are essential. After graduation from LASE students start to work as coaches, sports managers or recreation specialists, and, speaking about their employability, in their jobs foreign language competence is very significant. The aim of the research is to determine the demand among students for optional foreign language study courses, which foreign languages are chosen and studied by the LASE students. In the research, optional foreign language study course examination protocols were analyzed for the last four years, which provide the best indicator of how many students not only chose but also actually completed optional foreign language study courses. The research shows that at LASE the optional study courses of foreign language learning are in great demand in sport science direction. LASE students are aware of advantages of foreign language knowledge and skills in labor market also in sport sector and show their wish to continue developing their foreign language competence while studying at LASE.